In Vitro Assessment of Some Sperm Function Following Exposure to Levonorgestrel in Human Fallopian Tubes - Croxatto -Avoni, H (2012)
Background: The mechanism of action of levonorgestrel (LNG) as emergency contraception (EC) remains a subject of debate and its effect on sperm function has been only partially explained. The aim of this study was to assess whether LNG at a similar dose to those found in serum following oral intake for EC could affect spermatozoa when exposed to human fallopian tubes in vitro.Methods: Fifteen mini-laparotomies were performed, the side on which ovulation occurred was recorded, and both tubes were removed and perfused with a suspension containing 1 × 10(6) motile spermatozoa, with or without LNG. Following 4-hour incubation, the tubes were sectioned to separate the isthmus and the ampulla. Each segment was flushed and the material was evaluated to quantify the number of motile sperm, the number of spermatozoa adhering to the oviductal epithelium and the acrosome reaction (AR) rate.Results: The addition of LNG did not significantly alter the number of recovered motile spermatozoa either at the isthmus or at the ampulla, nor did it have any effect on the number of recovered spermatozoa adhered to the human tubal epithelium. Furthermore, LNG did not affect the AR rate. No significant differences were found even when the side on which ovulation occurred was taken into account.Conclusions: In a similar dose to that observed in serum following oral intake for EC, LNG had no effect on the number of motile spermatozoa recovered from the human fallopian tubes in vitro, on their adhesion to the tubal epithelium, distribution or AR rate. The possible effect of LNG as EC on sperm function remains poorly understood. © 2012 Hermanny et al; BioMed Central Ltd.